Delayed gadolinium-enhanced magnetic resonance imaging and T2 mapping of cartilage of the distal metacarpus3 / metatarsus3 of the normal Thoroughbred horse - Lammentausta, Evelina (University of Pretoria, 2014)
Thesis (PhD)--University of Pretoria, 2013.